Photometric And Spectroscopic Analysis Of The Sx Phe Star Bl Cam - Abdel-Sabour, M. A.; Nouh, M. I.; Shokry, A.; Hamed, G. M.; Ismail, H. A.; Takey, A.; Ata, S. A.; Zead, I. (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
In the present paper, we report the photometric and spectroscopic observations of the pulsating star BL Cam obtained by the 1.88 m telescope at the Kottamia astronomical observatory (KAO). Fourier analysis of the light curves indicates one frequency, 25.14427 c/d, with harmonics 51.112 c/d, 33.388 c/d, and 17.72464 c/d. The frequency of 31-32 c/d reported in the literature is not detected in our data except for one close to 33.3882934 c/d. A total of 55 new times of maximum light have been presented. A new value of (1/P) dP/dt is estimated using the O-C diagram based on all newly obtained times of maximum light combined with those taken from the literature, assuming the periods are decreasing and changing smoothly. Using model atmosphere analysis, we computed the effective temperature and surface gravity as Teff = 7625 ± 300 K and logg = 4.30 ± 0.37. The bolometric magnitude Mbol = 2.335, radius R = 1.69 R , luminosity L = 0.957 L, the mass M = 1.68M, and pulsation constant Q = 0.025 days. Locations of the star on the M-R and M-L diagrams indicate that it is close to the ZAMS track and is an unevolved star. В настоящей работе представлены фотометрические и спектроскопические наблюдения пульсирующей звезды BL Cam, полученные 1.88- метровым телескопом в астрономической обсерватории Коттамия (KAO). Фурье-анализ кривых блеска показывает частоту 25.14427 ц/сут, с гармониками 51.112 ц/сут, 33.388 ц/сут и 17.72464 ц/сут. Частота 31-32 ц/сут, о которой сообщается в литературе, не обнаружена в наших данных, за исключением частоты, близкой к 33.3882934 ц/сут. В общей сложности представлено 55 новых максимумов блеска. Новое значение (1/P) dP/dt оценивается с использованием диаграммы O-C, основанной на всех вновь полученных временах максимумов в сочетании с периодами, взятыми из литературы, предполагая, что периоды уменьшаются и изменяются плавно. Используя модельный анализ атмосферы, вычислены эффективная температура и ускорение силы тяжести Teff = 7625 ±300 K и logg = 4.30 , ± 0.37 dex. Болометрическая величина Mbol = 2.335, радиус R =1.69R  светимость L= 0.957 L , масса =1,68 M , константа пульсации Q = 0.025 сут. Расположение звезды на диаграммах M-R и M-L указывает на то, что она находится близко к ZAMS и является не эволюционированной звездой.
Keywords: Astrophysics